The great conversation a reader's guide to great books of the western world - Adler, Mortimer Jerome 1902-2001 (Great books of the Western world (1990), 1990)
Discusses the selection of works for and purpose of the set "Great Books of the Western World" and provides tools for use with the set, including author-to-idea and idea-to-author indexes and a ten-year reading list.